PENGARUH LATIHAN INTERVAL TRAINING TERHADAP KECEPATAN (SPEED) PADA TIM FUTSAL SMKN 5 PEKANBARU - Hendro Pandapotan Sitorus; Ramadi Ramadi; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purpose of this research is to find out if there is the influence of exercise interval training on the speed of the futsal team vocational schools of 5 Pekanbaru. The design of this study uses a group of the research is wearing the approach one group pretest-posttest design , with a population team futsal vocational schools of 5 Pekanbaru, the data in this research is the whole population of 12 people. The sample in this study, using a technique the total sampling are used is a sample of saturated and that’s where all the population as a sample. The instruments used in this research is a test acceleration of 30 meters, that aims to measure the speed in futsal. After that, the data is processed with statistics,to test normality with a lilifors test at significance level α (0.05). The hypothesis put forward is the influence of the interval training on speed. Based on the analysis of statistical data, the data pree test Lhitung of 0,1964 data post test Lhitung of 0,2324 and Ltabel 0,242, then Lhitung < Ltabel. Based on data analysis pree-test and post-test there are differences in the numbers are rising or an increase of 0,16 . Based on t test analysis produces Ttabel >Thitung of 16 and 1,796, meaning Thitung> Ttabel. Thus, there is the influence of exercise a distance of accuracy of interval training on speed of the futsal team vocational schools of 5 Pekanbaru.Keywords: A Interval Training, A Speed.